2016
DOI: 10.5897/ajmr2015.7832
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes in food: Control by monitoring the food processing environment

Abstract: Listeria monocytogenes is a foodborne pathogen that is widely dispersed in the environment; it is found in soil, water and plant material, and can grow at refrigeration temperature and at unfavourable conditions of pH (up to pH 4.7) and salt (up to 10%). It can persist in the harsh conditions of the food processing environment from which it can contaminate food. Listeriosis, infection with L. monocytogenes, can be mild but the ability of the pathogen to cross the epithelial barrier of the intestinal tract, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Sulfonamide resistance is raised by mutations in the folP gene encoding dihydropteroate synthase (DHPS) enzyme (Skold, 2001;Grape, 2006). These collective findings indicated that Chinese isolates conferred the resistance to important clinical drugs such as b-lactams, aminoglycosides, and erythromycin class; b-lactam class is the primary therapeutic option for human listeriosis together with aminoglycosides (Leong et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Sulfonamide resistance is raised by mutations in the folP gene encoding dihydropteroate synthase (DHPS) enzyme (Skold, 2001;Grape, 2006). These collective findings indicated that Chinese isolates conferred the resistance to important clinical drugs such as b-lactams, aminoglycosides, and erythromycin class; b-lactam class is the primary therapeutic option for human listeriosis together with aminoglycosides (Leong et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Canada, Australia and New Zealand adopted microbiological standards similar to those of Europe as recommended by CAC (Jadhav 2015 ). The US has zero tolerance policy for L. monocytogenes in RTE food products and food-processing facilities and failure to comply is considered a serious offence (Piet et al 2016 ).…”
Section: Legislations Relating To Listeria Monocytogenes mentioning
confidence: 99%
“…Faeces shed by infected animals along with silage are vehicles for primary infection in ruminants and reintroducing of L. monocytogenes into the environment (Lekkas 2016 ). Asymptomatic shedding of L. monocytogenes by infected animals can also transmit this pathogen to human beings through food (Piet et al 2016 ). Other sources of L. monocytogenes in a farm include poor animal husbandry, natural water and wastewater source.…”
Section: Occurrence Of Listeria Monocytogenes In Mmentioning
confidence: 99%
“…The possibility of “polony” still serving as a vehicle and promoter of growth for L. monocytogenes in consumers cannot be ignored. The presence of L. monocytogenes could be attributed to the contamination of “polony” before and during production and distribution and within the retail environments of this commodity due to the ubiquitous presence of this foodborne pathogen [ 68 ]. Listeria monocytogenes contaminated 16.7% of our study's “polony” samples.…”
Section: Discussionmentioning
confidence: 99%